MEMBINA KINERJA GURU BIMBINGAN DAN KONSELING DAN KONSELOR MELALUI PELATIHAN STRATEGI LESSON STUDY - Ujang Saprudin (Jurnal Penelitian Bimbingan dan Konseling, 2017)
The purpose of this study so that teachers BK / Counselor able to improve performance on an ongoing basis that impact on improving the quality of school guidance and counseling services. The method used is to verify the analysis of each competency indicator of teacher performance appraisal results, then conducted coaching performance of teachers BK / Counselor with lesson study strategy. The reason for applying the lesson study strategy is because it is effective, cheaper, closer, and improves teachers' willingness in self-evaluation and consultation with school supervisors. Stages in Lesson Study: (1) plan (planning); (2) do (implementation); (3) see (reflection and follow-up). The number of respondents involved 10 teachers BK / Counselor from 35 people BK / Counselor SMA on MGBK SMA Kota Cilegon. The indicators of successful performance coaching with this lesson study strategy indicate that 90% of the subjects have good and 10% perform well. The results of coaching also indicate that through the strategy of lesson study also there is a change of teacher performance value that the original value is very good to be average. Thus it can be concluded that the strategy of Lesson Study significantly influence positively to the improvement of performance of BK / Konselor teacher.  Keywords: Lesson study strategy, performance of BK / Konselor teachers